2018
DOI: 10.4066/2591-7951.1000049
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia in Children with Congenital Heart Disease and the Usefulness of Erythrocyte Indexes as a Screening Tool.

Abstract: Introduction: The iron deficiency anemia (IDA) is the most common micronutrient malnutrition in the world. This condition has been shown to increase morbidity in adults and to exert negative impact on the psycho-motor development in children. The IDA in children with congenital heart disease (CHD) with its negative consequence has been recognized for a long time but in clinical practice the issue does not gain sufficient attention in developing countries.Objectives: We conducted this study to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…No difference was observed between study groups in terms of age and gender (p>0.05). Binh TQ et al, 18 in their study observed majority of cases between 1-5 years with mean age of 2.9 years. Equal gender distribution was noted in the study.…”
Section: Demographymentioning
confidence: 83%
“…No difference was observed between study groups in terms of age and gender (p>0.05). Binh TQ et al, 18 in their study observed majority of cases between 1-5 years with mean age of 2.9 years. Equal gender distribution was noted in the study.…”
Section: Demographymentioning
confidence: 83%
“…This may result in an increased erythrocyte count and elevated blood viscosity, which contributes to the depletion of iron stores [ 7 ]. Even though polycythemia is associated with children who have cyanotic CHD, mostly both acyanotic and cyanotic children have the same high risk of having iron store depletion and iron deficiency anemia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%